Nutrient composition, in vitro true digestibility and methane production potential of feed resources of North Western Himalayan region - KANNAN, A; BHAR, R; RADOTRA, S; MAL, G; SINGH, B; JADHAV, R V; KUMAR, MANJEET; GAURAV, ALOK (The Indian Journal of Animal Sciences, 2017)
The present study assessed the nutrient composition, in vitro digestibility and methane production potential of the commonly fed feed resources of North Western Himalayan region. The feed resources were collected from different parts of North Western Himalayan region and dried at 60Â°C until constant weight and used for further analysis. The in vitro digestibility and methane production potential were determined using the in vitro gas production technique. The results indicated that in concentrates, cereal grains had significantly high ME value, high digestibility,low methane production potential and low methane energy loss as compared to brans. In roughages, tree fodders, had significantly high digestibility, high ME value, low methane production potential and low methane energy loss as compared to grasses and crop residues. In this study, there was strong negative correlation between OM and methane production; and strong positive correlation between ash, lignin, ADF, cellulose and NDF contents and methane production in concentrates. In contrast to concentrates, in roughages strong positive relationship wasobserved between OM contents and methane emission. Positive correlations between NDF, HC, cellulose and methane production; and negative relationship between methane production and lignin, ash and EE contents were also observed in roughages. Regression equations developed for predicting methane production showed high level of predictability for concentrates as compared to roughages. The data on nutrient composition, methane production potential reported for various feedstuffs in this study could be utilized judiciously in formulating low methaneemission diets for feeding ruminants in the region.